Esteticizem, antiesteticizem, anesteticizem - odsev pluralizma vrednot sodobne estetike v stilu poljske proze konca 20. stoletja - Witosz, Bożena (Slavistična revija, 2002)
The author argues for the necessity of considering the cultural context in research of modern literature and points out the category of pluralism or "non-hierarchical diversity", typical of the modern culture in the most recent decade. Within the style of Polish prose of the 1990's she discovers opposing tendencies: aestheticization, intellectualizaion and emphasis of ugliness, banalization, as vulgarization of language on the one hand and its intellectualization on the other. The author compares these to similar phenomena in the present-day culture: aestheticization of reality, aesthetics of nostalgia and "new brutality", anti-aesthetics, and crossing the limits of traditional value canon.
Keywords: anesteticizem; antiesteticizem; culture; esteticizem; kultura; pluralizem; Polish literature; poljska književnost; poljska proza; vrednote